The Effect of Cooperative Learning Approach, Competitive and Physical Fitness on Basketball Dribble Skills - I Ketut Hendry Wijaya Kusuma (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The condition of learning basketball games in physical education in junior high schools (SMP) is still not optimally carried out in the implementation of the teaching and learning process, especially in the context of developing learning outcomes of basketball skills. The method used in this research is an experimental method with Anava 2 x 2 design. The population in this study were seventh grade students of SMP Negeri 2 Sawan as many as 78 students. The sampling technique uses the Verducci technique, to be as many as 78 people according to what is needed in the study.The instrument chosen by the author is the physical fitness test from AAHPERD for the junior high level and for basketball dribbling skills with a validity level of 0.89, namely the dribble test from Horrison. The author's hypothesis in this study is (1) The learning outcomes of students' basketball skills taught through the Cooperative learning approach are better than the Competitive learning approach as a whole. (2) There is an interaction between learning approaches and physical fitness on learning outcomes of basketball skills. (3) The learning outcomes of basketball skills of student groups taught through the Competitive learning approach are better than those of student groups taught through the Cooperative learning approach in groups of students who have high fitness. (4) The learning outcomes of basketball skills of student groups taught through the Cooperative learning approach are better than those of student groups taught through the Competitive learning approach in groups of students who have low fitness.